A Review of Nonbiodegradable and Biodegradable Composites for Food Packaging Application - Aina Aqila Arman Alim; Siti Salwa Mohammad Shirajuddin; Farah Hannan Anuar (Journal of Chemistry)
The dependency on nonbiodegradable-based food packaging, increase in population growth, and persistent environmental problems are some of the driving forces in considering the development of biodegradable food packaging. This effort of green packaging has the potential to solve issues on plastic wastes through the combination of biodegradable composite-based food packaging with plant extracts, nanomaterials, or other types of polymer. Modified biodegradable materials have provided numerous alternatives for producing green packaging with mechanical strength, thermal stability, and barrier performance that are comparable to the conventional food packaging. To the best of our knowledge, the performance of nonbiodegradable and biodegradable composites as food packaging in terms of the above properties has not yet been reviewed. In this context, the capability of biodegradable polymers to substitute the nonbiodegradable polymers was emphasized to enhance the packaging biodegradation while retaining the mechanical strength, thermal stability, barrier properties, and antioxidant and antimicrobial or antibacterial activity. These are the ultimate goal in the food industry. This review will impart useful information on the properties of food packaging developed from different polymers and future outlook toward the development of green food packaging.